2020
DOI: 10.1136/bmjno-2019-000034
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonism in the psychiatric setting: an update on clinical differentiation and management

Abstract: Parkinsonism is seen frequently in patients with psychiatric conditions. Drug-induced parkinsonism (DIP) is the second most common cause of parkinsonism in the general population after Parkinson’s disease (PD) but a range of rarer aetiologies, some of them reversible, should also be considered in patients of all ages. DIP is more common in older patients, as are neurodegenerative diseases that may produce parkinsonism and it is relatively more likely that drug exposure could be unmasking an underlying process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Older adults may also have an increased sensitivity to the anticholinergic effects of APs leading to constipation, blurred vision, dry mouth, and urinary retention [81]. Urinary symptoms (urgency, frequency, and nocturia), sleep disturbances (daytime sleepiness, restless legs), concentration problems, sexual dysfunction, and olfactory dysfunction, have all been significantly associated with IPD compared to DIP [4,6,69,80,82]. Olfactory impairment, in particular, is very prevalent in IPD [6,82] and represents an early sign of neurodegeneration; but it is not a common symptom of DIP [69], although this has been reported [83].…”
Section: Non-motor Signsmentioning
confidence: 99%
See 4 more Smart Citations
“…Older adults may also have an increased sensitivity to the anticholinergic effects of APs leading to constipation, blurred vision, dry mouth, and urinary retention [81]. Urinary symptoms (urgency, frequency, and nocturia), sleep disturbances (daytime sleepiness, restless legs), concentration problems, sexual dysfunction, and olfactory dysfunction, have all been significantly associated with IPD compared to DIP [4,6,69,80,82]. Olfactory impairment, in particular, is very prevalent in IPD [6,82] and represents an early sign of neurodegeneration; but it is not a common symptom of DIP [69], although this has been reported [83].…”
Section: Non-motor Signsmentioning
confidence: 99%
“…Urinary symptoms (urgency, frequency, and nocturia), sleep disturbances (daytime sleepiness, restless legs), concentration problems, sexual dysfunction, and olfactory dysfunction, have all been significantly associated with IPD compared to DIP [4,6,69,80,82]. Olfactory impairment, in particular, is very prevalent in IPD [6,82] and represents an early sign of neurodegeneration; but it is not a common symptom of DIP [69], although this has been reported [83]. It has been suggested that olfactory function tests may be a useful tool in the differential diagnosis between DIP and IPD [84], and also in the diagnosis of "masked" IPD in patients with DIP [6] who do not seem to recover after withdrawal of the offending drug.…”
Section: Non-motor Signsmentioning
confidence: 99%
See 3 more Smart Citations